Small molecular push–pull donors for organic photovoltaics: effect of the heterocyclic π-spacer. Issue 124 (30th November 2015) - Labrunie, Antoine; Jiang, Yue; Baert, François; Leliège, Antoine; Roncali, Jean; Cabanetos, Clément; Blanchard, Philippe
Abstract : A series of (D–π–A) small push–pull molecules involving a triphenylamine electron-rich group (D) connected to a dicyanovinyl electron-deficient unit (A) through different chalcogenophene type π-connectors has been synthesized. Abstract : A series of (D–π–A) small push–pull molecules involving a triphenylamine electron-rich group (D) connected to a dicyanovinyl electron-deficient unit (A) through different chalcogenophene type π-connectors has been synthesized. Optical and electrochemical results reveal that the replacement of furan by thiophene and selenophene leads to a progressive decrease of the optical band gap of the material and to a parallel increase of hole mobility and power conversion efficiency (PCE). Thus, a PCE of 3.33% has been obtained for a simple air-processed solar cell involving the selenophene-based donor and the [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM) as the acceptor.